2007
DOI: 10.1353/rhe.2007.0028
|View full text |Cite
|
Sign up to set email alerts
|

Social Class and Belonging: Implications for College Adjustment

Abstract: This study addressed the extent to which social class position structures a sense of belonging at college, and the ways in which belonging informs adjustment to college. Among 322 liberal arts college students, social class background was significantly associated with a sense of belonging at college and was marginally related to academic performance but was not related to the quality of the experience they were having at college. Sense of belonging mediated the relationship between class background and adjustm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
327
1
12

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 380 publications
(361 citation statements)
references
References 64 publications
21
327
1
12
Order By: Relevance
“…In particular, Croizet and Claire (1998) found performance decrements among lower SES French students under a situation of identity threat. More recently, this effect was demonstrated in a sample of college students in the United States (Spencer & Castano, 2007).In addition to this work on academic performance, SES has been found to influence social and emotional well-being in the context of higher education (Ostrove & Long, 2007). For instance, in a retrospective study, Ostrove (2003) found that women from lower and middle-class backgrounds reported feeling more alienated or belonging less during their time spent at an elite college-echoing Walton and Cohen's (2007) work on the effects of racial underrepresentation at elite private universities.…”
mentioning
confidence: 71%
“…In particular, Croizet and Claire (1998) found performance decrements among lower SES French students under a situation of identity threat. More recently, this effect was demonstrated in a sample of college students in the United States (Spencer & Castano, 2007).In addition to this work on academic performance, SES has been found to influence social and emotional well-being in the context of higher education (Ostrove & Long, 2007). For instance, in a retrospective study, Ostrove (2003) found that women from lower and middle-class backgrounds reported feeling more alienated or belonging less during their time spent at an elite college-echoing Walton and Cohen's (2007) work on the effects of racial underrepresentation at elite private universities.…”
mentioning
confidence: 71%
“…A l'inverse, les étudiants de classe populaire feraient l'expérience d'un décalage culturel entre leurs normes culturelles plutôt interdépendantes et les normes d'indépendance institutionnalisées à l'université. L'université serait perçue comme n'étant pas un endroit pour eux, et ils questionneraient leurs chances de réussite (Johnson, Richeson, & Finkel, 2011;Ostrove & long, 2007).…”
Section: Approche Socioculturelle De La Classe Socialeunclassified
“…However, in the recent past a growing literature in the social psychology of education starts to take into account students' subjective perception of their social class (see for example Ostrove & Long, 2007;Ostrove, Stewart, & Chetan Sinha * Measurement issues of the social class in social psychology of education:…”
mentioning
confidence: 99%